Gene Expression Profiling in Viable but Nonculturable (VBNC) Cells of Pseudomonas syringae pv. syringae - Postnikova, Olga A.; Shao, Jonathan; Mock, Norton M.; Baker, Con J.; Nemchinov, Lev G. (Frontiers in Microbiology, 2015)
Pseudomonas syringae infects diverse crop plants and comprises at least 50 different pathovar strains with different host ranges. More information on the physiological and molecular effects of the host inhibitory environment on the pathogen is needed to develop resistant cultivars. Recently, we reported an in vitro model system that mimics the redox pulse associated with the oxidative burst in plant cells inoculated with Pseudomonas syringae pv. syringae. Using this system, we demonstrated that oxidation of acetosyringone, a major extracellular phenolic compound induced in some plants in response to bacteria, rendered Pseudomonas syringae. pv. syringae to a “viable but nonculturable” (VBNC) state. Here we performed a large scale transcriptome profiling of P.s.pv. syringae in the VBNC state induced by acetosyringone treatment and identified bacterial genes and pathways presumably associated with this condition. The findings offer insight into what events occur when bacterial pathogens are first encountered and host defense responses are triggered. The acquired knowledge will improve our understanding of the molecular mechanisms of stress tolerance. We believe that this is the first work on global gene expression profiling of VBNC cells in plant pathogenic bacteria.